Distribution of eigenvalues and trace formula for the Sturm–Liouville operator equation - Aslanova, N. M.; Bairamogly, M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study the asymptotic distribution of eigenvalues of the problem generated by the Sturm–Liouville operator equation. A formula for the regularized trace of the corresponding operator is obtained.